Hubungan Asupan Serat dengan Kontrol Glikemik pada Pasien Diabetes Melitus Tipe 2: Tinjauan Literatur - Fitri Firdausil Ma'wah; Farapti Farapti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Type 2 diabetes mellitus is a global health problem with increasing prevalence and a high risk of complications due to poor glycemic control. Dietary fiber intake plays an important role in maintaining blood glucose stability by slowing glucose absorption and improving insulin sensitivity. This study aims to analyze the relationship between fiber intake and glycemic control in patients with type 2 diabetes mellitus using a literature review approach. Articles were obtained from Google Scholar, PubMed, and ScienceDirect based on relevant keywords, with inclusion criteria including full-text research articles published within the last 10 years that examined fiber intake and glycemic control. The selected studies were analyzed descriptively. The findings indicate that most studies reported a significant relationship between higher fiber intake and better glycemic control, reflected in lower fasting blood glucose and HbA1c levels. Intervention studies also showed that increased consumption of fiber, particularly soluble fiber and vegetables, contributed to improved glycemic outcomes, although some studies reported no direct association due to variations in study design, sample size, type of fiber, and glycemic indicators used. Adequate fiber intake can therefore support glycemic control and should be considered as part of dietary management in patients with type 2 diabetes mellitus.